The Effect of Income On The Selection of The Price of Wall Painting Materials In Low Income Community Home Construction (MBR) - Ratika Isti, Adelina; Sugini, Sugini (Devotion : Journal of Research and Community Service, 2022)
Indonesia is no longer a developing country, but has grown gradually to become a developed country. In fact, according to The Office of the United States Trade Representative (USTR), which released the official release on Saturday 22 February 2020, Indonesia is no longer in the developing country category. The Ministry of Public Works and Public Housing (PUPR) admits that housing development for low-income people (MBR) is currently experiencing a number of obstacles. This study aims to determine the effect of income on the price of wall paint materials. The methodology to be used in this study is a rationalistic quantitative methodology. Quantitative research method is research that is full of nuances of numbers in data collection techniques in the field. Quantitative research has characteristics namely hard sciences, 'brief' and narrow focus, reductionistic, logical and deductive reasoning, knowledge base: causal relationships testing theories, control over variables, instruments, basic elements of analysis: numbers, statistical data analysis, generalization Based on statistical tests using the IBM SPSS application, the results obtained are in the form of a very strong influence between monthly income on the choice of wall paint material prices in the construction of houses for Low Income Communities (MBR).